VISION 2030: SAUDI ARABIA’S MODERNIZATION - Nadiya Azahra Hidayat; Yon Machmudi; Siti Rohmah Soekarba (Arabic Literature Department, 2022)
The Saudi Arabia Kingdom has a long history of applying Islamic law as a reference for state policies. The modernization that has taken place in Saudi Arabia certainly intersected with Wahhabism, adopted as the central ideology of the Saudi Arabia Kingdom. This study discusses Saudi Arabia's modernization efforts, which were initiated by Muhammad bin Salman’s Vision 2030. This study was designed with a descriptive-qualitative research method and used a literature review as the data collection technique. The theories used include Talcott Parsons' structural, functional theory with a decision-making process approach and the modernization theory by Inglehart and Welzel. The results revealed that the reign of King Salman and the Saudi Arabia Kingdom implemented Vision 2030 as a modernization of Muhammad bin Salman. Saudi Arabia's administration has gone through considerable changes from time to time. Societies once known to be conservative were able to quickly implement the economic and social reforms that began to lead to a liberal system. This is owing to the king's great power and the assurance of state welfare.